2013
DOI: 10.1155/2013/743018
|View full text |Cite
|
Sign up to set email alerts
|

A New Weak Chelator in Endodontics: Effects of Different Irrigation Regimens with Etidronate on Root Dentin Microhardness

Abstract: This study investigated the effect of sodium hypochlorite (NaOCl), ethylenediaminetetraacetic (EDTA), etidronic (HEBP), and citric acid (CA) associated in different irrigation regimens on root dentin microhardness. Forty-five root halves of single-rooted teeth were sectioned into thirds that were embedded in acrylic resin, polished, randomly assigned into 3 groups, and treated as follows: G1: saline solution; G2: 5% NaOCl + 18% HEBP, mixed in equal parts; and G3: 2.5% NaOCl. After measurements, the G3 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 28 publications
2
26
0
2
Order By: Relevance
“…These results are in agreement with those of several previous studies, 8,12,27,28,29 in which these solutions also reduced microhardness. This effect is desirable in the layer next to the canal lumen and it has been associated with increasing calcium loss, resulting in dentin demineralization and softening.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with those of several previous studies, 8,12,27,28,29 in which these solutions also reduced microhardness. This effect is desirable in the layer next to the canal lumen and it has been associated with increasing calcium loss, resulting in dentin demineralization and softening.…”
Section: Discussionsupporting
confidence: 93%
“…Knoop hardness was significantly higher for superficial dentin than for deep dentin, 26 presenting sensitivity to surface effects and textures, 13 suggesting that superficial dentin, closer to the pulp, should be analyzed with this method. 27 As in the present study, the Knoop indenter was used in previous investigations to evaluate changes in dentin microhardness. 13,27 Some studies in the literature have evaluated changes in dentin microhardness after canal irrigation with different solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, sealer retention should be different at cervical to apical third. However, Tartari et al (22) and Macedo et al (14) reported that despite differences in the structure of the roots thirds, the resulting alterations were found to be similar. Our results differ from the previous evaluations and could be explained by the differences within the internal root anatomy, as the apical third present a narrow filled space and could represent a difficult area to the sealer dislodgment.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, understanding the characteristics of the irrigated dentin surface is essential in obtaining adhesion of endodontic sealers that have different physicochemical characteristics. 28 In this study, the effects of EDTA laser agitation with different wavelengths on root dentin microhardness and roughness were evaluated and then compared with EDTA alone and EDTA with manual agitation.…”
Section: Discussionmentioning
confidence: 99%